Influence of device to device interconnection elements on the system behavior and stability - Iraj Sadegh Amiri; Ahmed Nabih Zaki Rashed; Preecha Yupapin (Institute of Advanced Engineering and Science, 2020)
This work has presented the interaction between tangential/sagittal cylindrical thin lens in the titled plane parallel crystal. Stability criterion parameters are measured under the control of curvature radius of a spherical mirror, the thickness of the tilted plane crystal, the refractive index of tilted plane crystal, the thickness for a plate of matter and phase angle of the sagittal cylindrical thin lens. Beam radius waist is plotted against the focal length of the tangential cylindrical thin lens. Focal length for both thin lens in resonator crystal is optimized to upgrade the resonator system operation efficiency.